KARIMBA: THE SHIFTING BOUNDARIES OF A SACRED TRADITION - Moon, Jocelyn (African Music : Journal of the International Library of African Music, 2018)
In Zimbabwe, urban musicians and educators often perceive karimba as a category of relatively small mbira that are used for secular entertainment. This notion is strongly influenced by the prominence of the Kwanongoma mbira, or nyunga nyunga mbira, a 15-key karimba that was first popularized by the Kwanongoma College of Music in the 1960s. Despite a wealth of research, very little has been written about karimba traditions around the Zimbabwe-Mozambique border that are associated with traditional religious practices. In this article, the author focuses on a type of karimba with more than 20 keys that shares much of the same repertoire with matepe/madhebhe/hera music in Rushinga, Mutoko, and Mudzi Districts in Zimbabwe and nearby regions in Central Mozambique. The author explores the connections between innovations of the Kwanongoma mbira and karimba traditions in the Northeast with examples from the International Library of African Music archival collections and her own ethnographic research. This article provides a foundation upon which others may further conduct research on karimba music and suggests possible directions for incorporating these findings into educational contexts.